New metathesis catalyst bearing chromanyl moieties at the N-heterocyclic carbene ligand - Hryniewicka, Agnieszka; Suchodolski, Szymon; Wojtkielewicz, Agnieszka; Morzycki, Jacek W.; Witkowski, Stanisław (Beilstein Journal of Organic Chemistry, 2015)
The synthesis of a new type of Hoveyda–Grubbs 2nd generation catalyst bearing a modified N-heterocyclic carbene ligands is reported. The new catalyst contains an NHC ligand symmetrically substituted with chromanyl moieties. The complex was tested in model CM and RCM reactions. It showed very high activity in CM reactions with electron-deficient α,β-unsaturated compounds even at 0 °C. It was also examined in more demanding systems such as conjugated dienes and polyenes. The catalyst is stable, storable and easy to purify.
Keywords: chromane derivatives; metathesis catalyst; nitrogen heterocycles; olefin metathesis; Ru-carbene

(untitled) - Fürstner, A. (Chem. Commun., 2011)

(untitled) - Nguyen, S. T.; Johnson, L. K.; Grubbs, R. H.; Ziller, J. W. (J. Am. Chem. Soc., 1992)

(untitled) - Vougioukalakis, G. C.; Grubbs, R. H. (Chem. Rev., 2010)

(untitled) - Endo, K.; Grubbs, R. H. (J. Am. Chem. Soc., 2011)

(untitled) - Keitz, B. K.; Endo, K.; Patel, P. R.; Herbert, M. B.; Grubbs, R. H. (J. Am. Chem. Soc., 2012)

(untitled) - Rosebrugh, L. E.; Herbert, M. B.; Marx, V. M.; Keitz, B. K.; Grubbs, R. H. (J. Am. Chem. Soc., 2013)

(untitled) - Occhipinti, G.; Hansen, F. R.; Törnroos, K. W.; Jensen, V. R. (J. Am. Chem. Soc., 2013)

(untitled) - Khan, R. K. M.; O'Brien, R. V.; Torker, S.; Li, B.; Hoveyda, A. H. (J. Am. Chem. Soc., 2012)

(untitled) - Buchmeiser, M. R. (Chem. Rev., 2009)

(untitled) - Klučiar, M.; Grela, K.; Mauduit, M. (Dalton Trans., 2013)

(untitled) - Kośnik, W.; Grela, K. (Dalton Trans., 2013)

(untitled) - Śledź, P.; Mauduit, M.; Grela, K. (Chem. Soc. Rev., 2008)

(untitled) - Szczepaniak, G.; Kosiński, K.; Grela, K. (Green Chem., 2014)

(untitled) - Pastva, J.; Skowerski, K.; Czarnocki, S. J.; Žilková, N.; Čejka, J.; Bastl, Z.; Balcar, H. (ACS Catal., 2014)

(untitled) - Scholl, M.; Ding, S.; Lee, C. W.; Grubbs, R. H. (Org. Lett., 1999)

(untitled) - Garber, S. B.; Kingsbury, J. S.; Gray, B. L.; Hoveyda, A. H. (J. Am. Chem. Soc., 2000)

(untitled) - Grela, K.; Harutyunyan, S.; Michrowska, A. (Angew. Chem., Int. Ed., 2002)

(untitled) - Chatterjee, A. K.; Choi, T.-L.; Sanders, D. P.; Grubbs, R. H. (J. Am. Chem. Soc., 2003)

(untitled) - Abbas, M.; Leitgeb, A.; Slugovc, C. (Synlett, 2013)

(untitled) - Abbas, M.; Slugovc, C. (Tetrahedron Lett., 2011)

(untitled) - Hryniewicka, A.; Morzycki, J. W.; Siergiejczyk, L.; Witkowski, S.; Wójcik, J.; Gryff-Keller, A. (Aust. J. Chem., 2009)

(untitled) - Hryniewicka, A.; Kozłowska, A.; Witkowski, S. (J. Organomet. Chem., 2012)

(untitled) - Hryniewicka, A.; Morzycki, J. W.; Witkowski, S. (J. Organomet. Chem., 2010)

(untitled) - Burton, G. W.; Doba, T.; Gabe, E. J.; Hughes, L.; Lee, F. L.; Prasad, L.; Ingold, K. U. (J. Am. Chem. Soc., 1985)

(untitled) - Burton, G. W.; Ingold, K. U. (Acc. Chem. Res., 1986)

(untitled) - Smith, L. I.; Renfrow, W. B., Jr; Opie, J. W. (J. Am. Chem. Soc., 1942)

(untitled) - Dean, F. M.; Matkin, D. A.; Orabi, M. O. A. (J. Chem. Soc., Perkin Trans. 1, 1981)

(untitled) - Mahdavian, E.; Sangsura, S.; Landry, G.; Eytina, J.; Salvatore, B. A. (Tetrahedron Lett., 2009)

(untitled) - Smith, L. I.; Hoehn, H. H.; Ungnade, H. E. (J. Org. Chem., 1939)

(untitled) - Suzuki, H.; Manabe, H.; Inouye, M. (Chem. Lett., 1985)

(untitled) - Choi, T.-L.; Lee, C. W.; Chatterjee, A. K.; Grubbs, R. H. (J. Am. Chem. Soc., 2001)

(untitled) - Funk, T. W.; Efskind, J.; Grubbs, R. H. (Org. Lett., 2005)

(untitled) - Choi, T.-L.; Chatterjee, A. K.; Grubbs, R. H. (Angew. Chem., Int. Ed., 2001)

(untitled) - Engelhardt, F. C.; Schmitt, M. J.; Taylor, R. E. (Org. Lett., 2001)

(untitled) - Wojtkielewicz, A.; Maj, J.; Morzycki, J. W. (Tetrahedron Lett., 2009)

(untitled) - Wojtkielewicz, A.; Maj, J.; Dzieszkowska, A.; Morzycki, J. W. (Tetrahedron, 2011)

(untitled) - Venuti, M. C. (Synthesis, 1982)

(untitled) - Hensle, E. M.; Tobis, J.; Tiller, J. C.; Bannwarth, W. (J. Fluorine Chem., 2008)

(untitled) - Stępień, D. K.; Cyrański, M. K.; Dobrzycki, Ł.; Wałejko, P.; Baj, A.; Witkowski, S.; Paradowska, K.; Wawer, I. (J. Mol. Struct., 2014)

(untitled) - Hryniewicka, A.; Misztalewska, I.; Czajkowska-Szczykowska, D.; Urbańczyk-Lipkowska, Z.; Morzycki, J. W.; Witkowski, S. (Tetrahedron, 2014)